The Policy of Human Organ Transplantation in Indonesia from the Perspective of Positive Law and Hindu Law - Widnyana, I Made Adi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2024)
Organ transplantation has been medically performed in the present day; however, the underlying thoughts regarding organ transplantation need to be examined by looking at studies sourced from ancient civilizations and teachings, as well as the positive laws that apply, particularly in Indonesia. The method used in this writing is based on normative research with a comparative, conceptual approach, as well as an approach to legislation. The results of this writing indicate that the regulation of organ transplantation in Indonesian positive law refers to the provisions of the WHO and the constitution in force in Indonesia, which legalizes its implementation with the obligation of obtaining consent from both the organ donor and the organ recipient, as well as a thorough examination of the conditions of both parties. In the study of Hindu law within the Bhagavad Gita, Upanishads, and other sources of Hindu law, there is no explicit regulation regarding organ transplantation. However, the epic Ithiasa indicates that organ transplantation was practiced in ancient times. Furthermore, based on the principles of Hindu teachings about ahimsa, dharma, and karma, the act of saving a life is considered a good deed that aligns with Hindu spiritual values. ansplantasi Organ secara medis telah dilakukan di masa sekarang, namun dasar pemikiran terkait dengan transplantasi organ perlu kita kaji dengan melihat kajian yang bersumber dari peradaban dan ajaran masa lampau serta hukum positif yang berlaku khususnya di Indonesia. Metode yang digunakan dalam penulisan ini bersumber dari penelitian normatif dengan pendekatan yang dilakukan secara komparatif, konseptual serta pendekatan terhadap peraturan perundang-undangan. Hasil penulisan ini menunjukkan bahwa pengaturan transplantasi organ dalam hukum positif Indonesia merujuk dari ketentuan WHO serta konstitusi yang berlaku di Indonesia yang melegalkan pelaksanaannya dengan kewajiban adanya persetujuan dari pendonor organ dan penerima organ serta pemeriksaan yang teliti terhadap kondisi keduabelahpihak. Dalam kajian hukum hindu didalam kitab Bhagawad Gita, Upanisad dan sumber Hukum Hindu lainnya secara eksplisit memang tidak mengatur khusus terkait transplantasi organ, namun dari epos ithiasa menunjukkan bahwa transplantasi organ pernah dilakukan pada masa dahulu, serta berdasarkan prinsip ajaran Hindu tentang ahimsa, dharma, dan karma tindakan menyelamatkan nyawa dianggap sebagai perbuatan baik yang sejalan dengan nilai-nilai spiritual Hindu.